Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1177/0894845315571412
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Career Growth in Chinese New Employee’s Turnover Process

Abstract: This study addresses the role of career growth in the turnover process among Chinese new employees. Based on reviews of the background of Chinese new employee combined with the Theory of Work Adjustment, we focus on career growth, person–organization fit (P-O fit), and job satisfaction as potential predictors. We examined career growth’s mediating effect between P-O fit and job satisfaction and its role in predicting turnover intention. Questionnaires were sent out through e-mail to Chinese new employees gradu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…In Nawaz and Pangil (2016), it was assumed that speed in employees' promotion have the potential to reduce employees' turnover intention, improve their commitment to the organisation and increase their sense of belongingness. Conversely, Karavarda (2014) and Chen et al (2016) found insignificant impact of career goal progress on employees' turnover intention in their different studies. Based on the aforementioned, the following hypotheses were formulated:…”
Section: Career Growth Opportunities and Turnover Intentionmentioning
confidence: 95%
See 1 more Smart Citation
“…In Nawaz and Pangil (2016), it was assumed that speed in employees' promotion have the potential to reduce employees' turnover intention, improve their commitment to the organisation and increase their sense of belongingness. Conversely, Karavarda (2014) and Chen et al (2016) found insignificant impact of career goal progress on employees' turnover intention in their different studies. Based on the aforementioned, the following hypotheses were formulated:…”
Section: Career Growth Opportunities and Turnover Intentionmentioning
confidence: 95%
“…In the same vein, Chen et al (2016) stated that availability of professional ability development for an employee in any organisation, has the potential to increase employee's satisfaction, and further improve the exchange relationship between the organisation and the employees. Hence, there will be little or no intention to leave such organisation.…”
Section: Career Growth Opportunities and Turnover Intentionmentioning
confidence: 99%
“…Given a lack of insights into employee career sustainability and employment instability in current economic conditions, we try to explore manufacturing workers' career sustainability from the perspectives of career growth and employability. To the best of our knowledge, the extant literature on CSRe explored its effects on organizational commitment [53,54], job satisfaction [55], etc., while research on career growth and employability focused on their relationships with organizational commitment [56] Sustainability 2019, 11, 4778 6 of 17 and turnover intention [57]. There is a dearth of empirical research examining the relationship between CSRe and career development sustainability.…”
Section: Conceptualizing Career Development Sustainabilitymentioning
confidence: 99%
“…In fact, many studies support that job satisfaction and organizational commitment predict intention to leave and intention to leave predicts actual turnover [38] . In addition few well reported predictors of intention to leave are impact of personality and type of job [39] , organizational justice , perceived career growth [40][41] , job characteristics [42][43], perceived organizational and supervisory support [44] , affective and normative commitment and goal clarity [45] , organizational climate, commitment and support [46]. However, this study will focus in detail the prediction of ITL through perceived organizational support and psychological contract fulfilment in the following sections.…”
Section: Intention To Leave (Itl) and Intention To Stay (Its)mentioning
confidence: 99%